Geomechanical processes during underground mining : proceedings of the School of Underground Mining, Dnipropetrov'k/Yalta, Ukraine, 24-28 September 2012 - Pivni︠a︡k, G. G. (CRC Press, 2012)
This volume deals with economic aspects of mining companies' development strategies, various mineral deposits development techniques, imitational modeling of mine workings with rock massif, methane extraction technologies during coal mining, geomechanical processes during plow mining, mining transport importance for mineral extraction, massif strain-stress state management using non-explosive destructing materials, and surface mining's detrimental influence on the environment. Special attention is paid to alternative ways of mining, such as borehole underground coal gasification for extraction.